Moving image - Kholeif, Omar; Bird, Robert (London : Whitechapel Gallery, 2015)
Jananne al Ani; Francis Alys; Uri Ancarani; Oreet Ashery; Ed Atkins; Judith Barry; Gretchen Bender; Dara Birnbaum; Black Audio Film Collective; Brad Butler; Olga Chernysheva; James coleman; Minerva; Cuevas; Stan Douglas; Olafur Eliasson; VALIE EXPORT; Harun Farocki; Omer Fast; Morgan Fisher; Hollis Frampton; Melanie Gilligan; Joana Hadjithomas; Gary Hill; Susan Hiller; William Kentridge; Anja Kirchner; Steve McQueen; Jumana Manna; Karen Mirza; Rabih Mroué; Otolith Group; Nam June Paik; Luther Price; Yvonne Rainer; R.V.Ramani; Pipilotti Rist; Ben Rivers; Tyan Trecartin; Trinh T. Minh-Ha; Bill Viola
Formerly CIP.
boek
Keywords: Art, Modern -- 21st century; Video art -- Technique; Video art -- Technological innovations; Performance art -- Technique; Performance art -- Technological innovations